The association between information technology sophistication and patient portal use: A cross sectional study in Eastern North Carolina - Asagbra, O Elijah; Burch, Ashley; Chivela, Fernando L. (Health Informatics Journal, 2023)
Even with the extolled benefits of patient portals, there has been some challenges to ensuring patient portal use. This study examines if a patient’s level of information technology (IT) sophistication, defined as the degree of use of diverse information technologies by an individual, is associated with their use of a patient portal. Patients previous experience and exposure to other similar technologies like desktop computer, laptop, internet, smart phone, or social media explains their willingness to use information technology for their health. Data on a cross-sectional survey of 565 individuals in Eastern NC was available for analysis. Multinomial regression analyses revealed that IT sophistication is important in determining whether patients will use a patient portal. It specifies that patients with low IT sophistication compared to those with high IT sophistication were more likely to have never activated their patient portals (RRR = 2.2155, p < 0.009), or to have activated but never used a patient portal (RRR = 3.5869, p < 0.010). The findings of this study should aid healthcare leaders as they strive to improve patient engagement. They should continue to promote the benefits of the patient portal and consider offering personalized support programs for patients with low IT sophistication.